DISTRIBUTION OF TRAVEL INSURANCE USER AMONG TRAVELERS VISITING BALI, INDONESIA - Putu Indah Budi Apsari; Putu Arya Suryanditha (Lembaga Penelitian, Universitas Warmadewa, 2022)
Travel insurance is important to protect travelers to various travel risk and health problem. But because of financial condition and lack of knowledge to protect their safety while traveling, the use of travel insurance is very low. This research aim to assess distribution of travel insurance user among travelers especially who visiting Bali as their destination trip. This is cross-sectional study using medical record of foreign travelers visiting international hospital. Result show most travelers have no travel insurance (70%) compared with people take travel insurance for their safety vacation. Based on age, there are no significance difference between age group 0-18 years, 19-64 years dan more that 65 years, approximately the youngest people the lack of awareness to buy travel insurance. Based on health problem the distribution of travelers with no travel insurance tend to be same on average 60-80%. As conclusion the use of travel insurance remains low, furthermore all travelers must be encouraged to use travel insurance for their safety.